Коэффициенты распределения в сложных полупроводниковых системах - Романенко В. Н. Владимир Николаевич; Саидов М. С. Мухтар Сафарбаевич; Абдукаримов Э. Т. Эркин Тухтаевич; Никитина Г. В. Галина Васильевна; Юнусов Махамаджан Сабирович (Ташкент, Фан, 1987)
Авт. указаны перед вып. дан.